Age Estimation from Fusion of Manubrium & Xiphoid Process with Sternal Body: A Radiological Study in Living Individuals from Central India - Ninad Nagrale1 , Swapnil Patond2 , Prakash Mohite3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Forensic Age Estimation is an expertise in Forensic Medicine which aims to find out the most accurate wayof determining the chronological age of the unknown person involved in judicial or legal proceedings. Thisstudy aims to investigate the relationship between the stage of union at Manubrium, Sternum & XiphoidProcess and biological age in Chhattisgarh population. The study was carried out in 270 healthy subjects(135 males and 135 females) aging from 25 to 70 years. The obtained results from the radiographs revealedthat the complete fusion of Xiphoid process & Manubrium with the body of sternum is seen in more than& 70% of individuals in the age group of 50-55 years. Females were consistently developing union at ayounger age than their male counterparts. Results also suggest that the age of union is found to vary greatlyall over the India indicating the need for separate standards of age of epiphyseal union for separate regions.